Dynamic 3D proteomes reveal protein functional alterations at high resolution in situ - Cappelletti, Valentina; Hauser, Thomas; Piazza, Ilaria; Pepelnjak, Monika; Malinovska, Liliana; Fuhrer, Tobias; Li, Yaozong; Dörig, Christian; Boersema, Paul; Gillet, Ludovic; Grossbach, Jan; Dugourd, Aurélien; et al. (Cell, 2021)
Biological processes are regulated by intermolecular interactions and chemical modifications that do not affect protein levels, thus escaping detection in classical proteomic screens. We demonstrate here that a global protein structural readout based on limited proteolysis-mass spectrometry (LiP-MS) detects many such functional alterations, simultaneously and in situ, in bacteria undergoing nutrient adaptation and in yeast responding to acute stress. The structural readout, visualized as structural barcodes, captured enzyme activity changes, phosphorylation, protein aggregation, and complex formation, with the resolution of individual regulated functional sites such as binding and active sites. Comparison with prior knowledge, including other ‘omics data, showed that LiP-MS detects many known functional alterations within well-studied pathways. It suggested distinct metabolite-protein interactions and enabled identification of a fructose-1,6-bisphosphate-based regulatory mechanism of glucose uptake in E. coli. The structural readout dramatically increases classical proteomics coverage, generates mechanistic hypotheses, and paves the way for in situ structural systems biology.
Das PDF enthält zusätzlich einen Anhang von 13 Seiten
Available online 23 December 2020
Gesehen am 08.09.2021